Multi-criteria evaluation of solid oxide fuel cell based combined cooling heating and power (SOFC-CCHP) applications for public buildings in China - Jing,R; Wang,M; Brandon,N; Zhao,Y (Energy, 2017)
This study aims to evaluate the feasibility of solid oxide fuel cell based combined cooling heating and power (SOFC-CCHP) applications in public buildings of China from different perspectives. Operations of the natural gas fueled SOFC-CCHP systems for 20 years’ have been simulated for five categories of public buildings in five locations of China. Parallel simulations of combustion based CCHP systems and conventional system have been conducted for comparison. By single criterion assessment, SOFC-CCHP systems demonstrate outstanding performance on energy efficiency as well as reducing carbon emission, air pollution and human health damage cost. The levelized cost of energy (LCOE) turns out to be competitive with commercial electricity price, but a long payback period (SPP) has also been identified. To further assess the overall performance of SOFC-CCHP systems, a multi-criteria assessment model has been developed by combining the gray relational analysis (GRA) approach and the entropy-weighting method. The result indicates that hospital, hotel, and supermarket achieve more benefits than office and school; warmer regions rank slightly higher than colder regions. In addition, sensitivity analysis has been performed on SPP and LCOE. Overall, this paper provides theoretical guidance and evaluation approach for SOFC-CCHP demonstrations in China.